POTENSI PEMANFAATAN LUMPUR DARI PROSES PENGOLAHAN AIR LIMBAH INDUSTRI - Galuh Retno Cahyaningnugroho; Euis Nurul Hidayah (Yayasan Nusantara Hasana Berdikari, 2023)
The liquid waste treatment process will produce another by-product, namely sludge or sludge. Sludge from WWTP is managed in a Sludge Drying Bed (SDB) unit with a drying system. utilization of sludge into a valuable product is an effort to reduce sludge discharged into the environment. The sludge can be utilized one of them as fuel in the form of briquettes. Utilization of sludge as compost is an alternative that can be done as an effort to manage the environment and has humus material and nutrient content. As well as mud as an alternative to providing nutrients in ultisol soil. Another use of sludge waste is to utilize toothpaste factory sludge as a raw material for brick making, because of its characteristics it contains SiO2 and CaO.